An apical ring protein essential for conoid complex assembly and daughter cell formation in Toxoplasma gondii - Li, Wei; Koczy, Oliwia; Qin, Peipei; Forné, Ignasi; Gras, Simon; Grünert, Jennifer; Klingl, Andreas; Mattei, Simone; Jimenez-Ruiz, Elena; Meissner, Markus (Nature Communications, 2025)
In Toxoplasma gondii, the conoid complex consists of intraconoidal microtubules (ICMTs), preconoidal rings (PCRs), apical polar ring (APR), and the conoid. This organelle plays an important role for initiation of gliding motility, required for host cell invasion and egress. The molecular mechanisms governing stepwise assembly of the conoid complex remain poorly understood. We previously identified CGP, an essential protein required for motility initiation. Here, we demonstrate that CGP is crucial for anchoring FRM1 and other PCR components to mature PCRs, while the initial assembly in daughter cells is unaffected. Cryo-electron tomography of CGP-depleted parasites reveals the absence of the PCRs in the mature parasites, demonstrating that CGP is essential for stabilising the PCRs after replication. Using CGP as bait, we identify a protein required for the early assembly of the nascent conoid complex. The APR scaffold assembly factor (ASAF1) defines the position of the conoid complex before tubulin polymerisation. Depletion of ASAF1 results in failure of conoid complex assembly, disorganised microtubules, and lack of daughter cell formation. Collectively, our findings reveal two essential proteins that play critical roles in the early and late stages of conoid complex formation, providing insight into the mechanisms of conoid complex assembly.
Online veröffentlicht: 28. November 2025
Gesehen am 27.02.2026